Reactivation Strategy: Reviving Forgotten Landfills - Sholihah, Iffahni (Solo Universal Journal of Islamic Education and Multiculturalism, 2024)
This research focuses on developing reactivation strategies for Al-Qur'an Learning Sites (TPA: Taman Pendidikan Al-Qur’an) that have been forgotten or have experienced a decrease in activity in the community. TPA, as a basic educational institution in the teaching of the Qur'an, plays an important role in shaping the religious and moral foundations of Muslim society. However, some landfills face challenges such as lack of resources, lack of participation, and loss of relevance to the younger generation. This study aims to identify the factors causing the decline in activity in landfills and develop a comprehensive strategy to revitalise them by involving new technologies, teaching methodologies, and community strengthening. Using a mixed methodology approach, this study combines qualitative data analysis from in-depth interviews with landfill managers, teachers, parents, and students, as well as quantitative questionnaires disseminated to the wider community. The study also explores case studies of successfully reactivated landfills to draw lessons and best practices. The results of the study show that landfill reactivation can be successful through the application of technology in learning, the development of an interesting and relevant curriculum, community marketing strategies to increase awareness and participation, and the establishment of a strong support network between landfills and other religious and educational institutions. In addition, this study emphasises the importance of training and professional development for teachers to improve the quality of Qur'an teaching.